Enhancement Quality Service of Secretariat Employees Through Service Excellent Training - Rubiyatno; Gregorius Hendra Poerwanto; Albertus Yudi Yuniarto; Patrick Vivid Adinata; Maria Theresia Ernawati; Aurelia Melinda Nisita Wardhani; Ima Kristina Yulita (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2022)
The community service aim to give understanding and practice on excellent service for employee at secretariat parishes, schools and foundations The methods of the community service is a participatory training by lectures and simulation of excellent service. The participants of the community service are very enthusiastic. In general, participants understand and can simulate excellent service seriously. Participants feel comfortable and happy because they can simulate excellent service in the right ways. Training went very well, participants understand the concept of excellent service and the importance to give excellent service, even while they are facing time limitation. In the future, employees at secretariat need to be continuously refreshed about excellent service and practice of excellent service.